An Audit of Preoperative Counselling and Informed Consent in Four Teaching Hospitals of Lahore, Pakistan - ZIAULLAH MALIK GHULAM MUSTAFA ARIAN, AHSAN NASIM (Journal of Fatima Jinnah Medical University, 2018)
Objective: To evaluate the ongoing practice of preoperative counselling and informed consent in teaching hospitals of Lahore, Pakistan. Settings: Surgical Units of Jinnah Hospital, Mayo Hospital, Services Hospital and Sir Ganga Ram Hospital of Lahore, Pakistan. Design: Prospective Observational Study. Duration: Six (06) Months, January 2011 to June 2011.